Field Assessment of Non-nuclear Methods Used for Hot Mix Asphalt Density Measurement - Zaman, Shah; Hussain, Jawad; Ahmad Zaidi, Syed Bilal; Ejaz, Naeem; Awan, Hammad Hussain (Salehan Institute of Higher Education, 2019)
Destructive nature along with the associated higher cost of the traditional core method used for hot mix asphalt density measurement has convinced researchers switching to some non-destructive technique for this purpose which is cost efficient as well. Earlier, nuclear density gauges were introduced for this purpose which was non-destructive as well. Since such devices were associated with the use of gamma rays, therefore, leading to safety and health issues. Last decade observed a revolution in asphalt density measurement technique with the evolution of non-nuclear density gauges. This research work is carried out with the objective to determine the efficiency and accuracy of a newly developed non-nuclear density gauge i.e. PQI-380 for field conditions as it needs its thorough evaluation prior to future uses in many of the developing countries including Pakistan. Density data obtained using standard core method and non-nuclear density gauge for 195 location confirms the satisfactory performance of the instrument. Results obtained show that the coefficient of correlation is near to 0.9. which refers to a strong correlation between the density data. Moreover, performance criteria e.g. root mean square error and mean absolute error between the density data set is also very low confirming the good measuring abilities of the device. Instrument performed well for repeatability analysis giving maximum coefficient of variance less than 5 percent.